Equality Concerns and the Limits of Self-Governance in Heterogeneous Populations - Lata Gangadharan; Nikos Nikiforakis; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2015)
Mechanisms to overcome social dilemmas provide incentives to maximize efficiency. However, often – such as when agents are heterogeneous – there is a trade-off between efficiency and equality. Agents' concerns for equality in such instances can limit the ability of mechanisms to promote efficiency. We provide evidence for this from a public good experiment using a simple mechanism which allows individuals to communicate periodically with other group members and reward them for their actions. We show that, in homogeneous populations – where there is no tension between efficiency and equality – the mechanism permits group to obtain maximum efficiency. This is not the case in heterogeneous populations where individuals derive different benefits from cooperation. Although almost all heterogeneous groups agree to follow specific contribution rules with positive contributions, most of them either prioritize equality over efficiency or strike a compromise between the two. These findings suggest that equality concerns can impose limits on the ability of heterogeneous populations to reach efficient outcomes through self-governance.
Keywords: C92; H41; D74; 330; communication; rewards; cooperation; normative conflict; heterogeneity